2008
DOI: 10.1159/000121400
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Genetic Outreach Education and Support to Primary Care on Practitioner’s Confidence and Competence in Dealing with Familial Cancers

Abstract: Aims: To determine the level of competence and confidence in general practice in relation to the management of familial cancers and to determine the impact of providing genetic educational outreach on confidence and competence. Methods: Confidence and competence in dealing with familial cancers was measured using a postal questionnaire sent to all general practitioners and practice nurses in 4 geographical areas in central England. In 2 areas, genetic educational outreach was provided to 10 randomly selected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Providers in primary care 56 and the range of physicians or surgeons in cancer care 57 may feel they lack adequate genetic knowledge or skills in this area. This, and challenges of communication, including language barriers, may be one reason those from ethnic minorities appear less likely to be referred to cancer genetics services.…”
Section: Discussionmentioning
confidence: 99%
“…Providers in primary care 56 and the range of physicians or surgeons in cancer care 57 may feel they lack adequate genetic knowledge or skills in this area. This, and challenges of communication, including language barriers, may be one reason those from ethnic minorities appear less likely to be referred to cancer genetics services.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found that primary care physicians’ ability to correctly assign risk was low, even in cases where they reported high levels of confidence in their ability to assign risk; specifically, half of primary care physicians incorrectly assigned a high-risk categorization to a low-risk case. 25 In another study using unannounced standardized (simulated) patients, satisfaction with physician communication was higher for moderate risk cases compared with high-risk case, 26 highlighting that many physicians are unprepared to address complex high-risk scenarios. Results suggest that educational training programs designed for frontline healthcare clinicians should focus on increasing the ability of clinicians to correctly identify risk level and make appropriate risk management recommendations (surveillance, screening, and referral for counseling).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that providing genetic educational outreach to doctors has a positive impact in improving their competency and confidence in the use of genetic testing to guide prevention or treatment decisions [68]. Although the importance of genomic education for health care professionals has been recognized even before completion of the Human Genome Project [9], many physicians do not feel to have a proper training and knowledge [3, 4].…”
Section: Introductionmentioning
confidence: 99%